Low-dielectric and high-peel-strength hydrocarbon resin, composition for copper-clad plate and preparation method of composition

By introducing phenolic hydroxyl groups and maleimide resin with good structural symmetry into the hydrocarbon resin, the bonding force and peel strength between the resin and the copper foil are improved, and the problem of insufficient peel strength of the existing hydrocarbon resin is solved. , realizing the preparation of high-performance copper-clad laminates.

CN119331151APending Publication Date: 2025-01-21SICHUAN DONGFANG INSULATING MATERIAL +1

Patent Information

Application Number
CN202411487764.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing hydrocarbon resins have excellent dielectric properties but low peel strength in copper clad applications, which limits their use range.

Method used

By polymerizing divinylbenzene and phenolic compounds containing double bonds in the presence of free radical initiators, polymerization inhibitors, and solvents, a hydrocarbon resin with low dielectric and high peel strength containing phenolic hydroxyl groups is synthesized and combined with Other high-performance resins, fillers, initiators, antioxidants, etc. are compounded to obtain a resin composition for copper clad laminates.

Benefits of technology

The hydrocarbon resin and copper-clad laminate composition achieves the characteristics of high peel strength, low dielectric constant, low dielectric loss, high glass transition temperature, etc., and is suitable for the preparation of high-performance copper-clad laminates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331151A_ABST
    Figure CN119331151A_ABST
Patent Text Reader

Abstract

The invention discloses a low-dielectric and high-peel-strength hydrocarbon resin as shown in a formula (3), a composition for a copper-clad plate and a preparation method of the composition. The preparation method is characterized in that divinyl benzene and a phenolic compound containing double bonds are subjected to a polymerization reaction in the presence of a free radical initiator, a polymerization inhibitor and a solvent to obtain the low-dielectric and high-peel-strength hydrocarbon resin; the resin composition for the copper-clad plate is prepared by uniformly mixing 100 parts by mass of hydrocarbon resin with low dielectric and high peel strength, 10-20 parts by mass of maleimide resin, 0.1-0.5 part by mass of an initiator, 0.1-0.5 part by mass of an antioxidant, 60-80 parts by mass of filler and 70-140 parts by mass of a solvent at the temperature of 30-50 DEG C. The composition for the low-dielectric and high-peel-strength hydrocarbon resin and the copper-clad plate has the characteristics of high peel strength, low dielectric constant, low dielectric loss and the like, is good in product performance, and is suitable for the fields of artificial intelligence, 5G base stations, power amplifiers, automobile radars and the like. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to a hydrocarbon resin for copper clad laminates, a composition and its preparation, and relates to a low dielectric, high peel strength hydrocarbon resin and a composition for copper clad laminates and a preparation method thereof. The low dielectric, high peel strength hydrocarbon resin and the composition for copper clad laminates of the present invention have the characteristics of high peel strength, low dielectric constant, low dielectric loss, etc., and are suitable for laminates, integrated circuit packaging, high-frequency and high-speed copper clad laminates, high-density Internet, artificial intelligence, 5G base stations, power amplifiers and automotive radars and other fields. Background Art

[0002] Benefiting from the rapid development of artificial intelligence, printed circuit board (PCB) products are driven to develop in the direction of high density, high performance, high frequency and high speed, and new requirements such as lower dielectric constant and lower dielectric loss are put forward for electronic substrate resins.

[0003] Among the many resins suitable for high-performance PCB products, hydrocarbon resin has good dielectric properties (volume resistivity 10 17~18 Ω·m; dielectric constant (1MHz) 2.4~2.8; tanδ 0.0002~0.0006), has received more and more attention in recent years. On the other hand, the low polarity of hydrocarbon resin (there are only carbon and hydrogen elements in the structure) also leads to poor bonding with copper foil and low peel strength, which limits its use.

[0004] CN 116925446A discloses "a high thermal conductivity hydrocarbon resin for copper-clad laminate and its preparation method". The provided high thermal conductivity hydrocarbon resin and resin copper-clad laminate have lower dielectric constant, lower dielectric loss and higher thermal conductivity, but their peel strength is lower, only 0.55-0.78N / mm.

[0005] CN 113980370A discloses "a high-hardness, high-peel-strength, yellowing-resistant hydrocarbon resin composition, and its preparation method and use". The high-hardness, high-peel-strength, yellowing-resistant hydrocarbon resin composition provided, the pressed copper clad laminate has a lower dielectric constant, lower dielectric loss, higher hardness and yellowing resistance, and although the peel strength is improved compared with ordinary hydrocarbon boards, it is still relatively low, at 1.21-1.33N / mm.

[0006] CN 112111074A discloses "a uniform dispersion of a cross-linkable hydrocarbon resin composition and a semi-cured sheet and a high thermal conductivity thermosetting copper-clad laminate prepared therefrom". The invention provides a uniform dispersion of a cross-linkable hydrocarbon resin composition, and the pressed copper-clad laminate has excellent dielectric properties, thermomechanical strength, and dimensional stability, but a relatively low peel strength of 0.83-0.98 N / mm.

[0007] The dielectric properties of hydrocarbon resins in the above-mentioned prior art are very excellent, but the peel strength is relatively low. If the bonding force between the resin and the interface and the peel strength can be increased while maintaining good dielectric properties, the application of hydrocarbon resins in the copper clad laminate field will be greatly expanded. Summary of the invention

[0008] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and provide a low dielectric, high peel strength hydrocarbon resin and a composition for copper clad laminates and a preparation method thereof. The present invention uses divinylbenzene and a phenolic compound containing a double bond to undergo a polymerization reaction in the presence of a free radical initiator, an inhibitor, and a solvent to synthesize a low dielectric, high peel strength hydrocarbon resin containing a phenolic hydroxyl group; then it is compounded with other high-performance resins, fillers, initiators, antioxidants, and solvents to obtain a resin composition for copper clad laminates. Thus, a hydrocarbon resin and a composition for copper clad laminates having the characteristics of high peel strength, low dielectric constant, low dielectric loss, high glass transition temperature, etc., which can be used as high-performance copper clad laminates, and a preparation method thereof are provided.

[0009] The present invention is a low dielectric, high peel strength hydrocarbon resin, characterized in that the low dielectric, high peel strength hydrocarbon resin (compound) has the chemical structural formula shown in (3):

[0010]

[0011] In formula (3), x is 10 to 40, y is 1 to 8, R3 is -CH3, and R4 is n=0, 1, 2, R5 is -OCH3;

[0012] In the content of the present invention: the number average molecular weight (Mn) of the low dielectric and high peel strength hydrocarbon resin ranges from 2000 to 8000, and the double bond content ranges from 20% to 60%;

[0013] The double bond content is defined as the percentage of the mass of double bonds contained in 1g of sample (ie, the hydrocarbon resin) to the total mass.

[0014] In the content of the present invention: the preparation method of the low dielectric, high peel strength hydrocarbon resin is: divinylbenzene and a phenolic compound containing a double bond undergo a polymerization reaction in the presence of a free radical initiator, an inhibitor, and a solvent to obtain a low dielectric, high peel strength hydrocarbon resin solution, and then the solvent and unreacted raw materials in the solution are evaporated to obtain the low dielectric, high peel strength hydrocarbon resin.

[0015] In the content of the present invention: the specific steps of the preparation method of the low dielectric and high peel strength hydrocarbon resin are:

[0016] The first step is to introduce nitrogen into a reactor equipped with a stirrer, a thermometer, and a condenser, add 1 mol of divinylbenzene, 0.1-0.5 mol of a phenolic compound containing a double bond, then add a free radical initiator of 0.1-2% of the total weight of the divinylbenzene and the phenolic compound containing a double bond, add a polymerization inhibitor of 0.01-1% of the total weight of the divinylbenzene and the phenolic compound containing a double bond, add a solvent of twice the total weight of the divinylbenzene and the phenolic compound containing a double bond, raise the temperature to 60-100° C., react for 1-10 hours, and obtain a hydrocarbon resin solution with low dielectric and high peel strength;

[0017] The second step is to maintain the distillation temperature at 60-100° C. and evaporate the solvent and unreacted divinylbenzene in the hydrocarbon resin solution by rotary distillation to obtain a low dielectric and high peel strength hydrocarbon resin;

[0018] The divinylbenzene is one of o-divinylbenzene, m-divinylbenzene and p-divinylbenzene or a mixture of two or more thereof;

[0019] The double-bond-containing phenolic compound is a compound containing a phenolic hydroxyl group, a double bond and a benzene ring structure, and has a chemical structure shown in formula (1):

[0020]

[0021] In formula (1): R1 is -CH=CH2, -CH2-CH=CH2, -C(=CH2)-CH3, -CH2-CH2-CH=CH2, -CH2-CH2=CH-CH2; R2 is -OCH3;

[0022] The free radical initiator is a peroxide or / and an azo compound initiator;

[0023] The polymerization inhibitor is a polyphenol polymerization inhibitor and / or a quinone polymerization inhibitor.

[0024] The free radical initiator may specifically be one or a mixture of two or more of diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, dicyclohexyl peroxydicarbonate, isopropylbenzene hydroperoxide, and azobisisobutyronitrile;

[0025] The polymerization inhibitor may specifically be one or a mixture of two or more of hydroquinone, p-tert-butylcatechol, 2,6-di-tert-butyl-p-methylphenol, p-benzoquinone, and 1,4-naphthoquinone;

[0026] The solvent is one of methanol, ethanol, tetrahydrofuran, toluene, xylene, petroleum ether, butanone, methyl isobutyl ketone or a mixture of two or more thereof.

[0027] Another aspect of the present invention is: a resin composition for copper-clad laminates, characterized in that: the resin composition for copper-clad laminates is prepared by mixing and stirring 100 parts by mass of a low-dielectric, high-peel strength hydrocarbon resin, 10 to 20 parts by mass of a maleimide resin, 0.1 to 0.5 parts by mass of an initiator, 0.1 to 0.5 parts by mass of an antioxidant, 60 to 80 parts by mass of a filler and 70 to 140 parts by mass of a solvent at 30 to 50° C. to obtain the resin composition for copper-clad laminates;

[0028] The solid content of the copper clad laminate composition is 58% to 75%;

[0029] The solid content is defined as the weight percentage of the solid content in the solution to the total solution.

[0030] The low dielectric and high peel strength hydrocarbon resin has a general chemical structure as shown in formula (4):

[0031]

[0032] In formula (4), x is 10 to 40, y is 1 to 8, R3 is -CH3, and R4 is n=0, 1, 2; R5 is -OCH3;

[0033] The low dielectric and high peel strength hydrocarbon resin has a number average molecular weight (Mn) ranging from 2000 to 8000 and a double bond content of 20% to 60%;

[0034] The double bond content is defined as the percentage of the mass of double bonds contained in 1g of sample (ie hydrocarbon resin) to the total mass.

[0035] The maleimide resin has a general chemical structure as shown in formula (5):

[0036]

[0037] In formula (5): R6, R7 are -H, -CH3, -C2H5;

[0038] The initiator is a peroxide or / and an azo compound initiator;

[0039] The antioxidant is one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], 2,6-di-tert-butyl-p-cresol, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate isooctyl alcohol ester, bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate][oxalylbis(azanediyl)]bis(ethane-2,1-diyl)ester, or a mixture of two or more thereof;

[0040] The filler is one or a mixture of two or more of montmorillonite, calcium carbonate, magnesium hydroxide, zinc borate, talc, aluminum hydroxide, kaolin, barium sulfate, silicon dioxide, silicon micropowder, mica powder, hollow glass microspheres, and fumed silica;

[0041] The solvent is one or a mixture of two or more of butanone, toluene, xylene, cyclohexanone, propylene glycol monomethyl ether, propylene glycol methyl ether acetate, N,N-dimethylformamide, N,N-dimethylacetamide, and methyl isobutyl ketone;

[0042] In the resin composition for copper-clad laminates, the initiator may be one or a mixture of two or more of diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, dicyclohexyl peroxydicarbonate, isopropylbenzene hydroperoxide, and azobisisobutyronitrile.

[0043] In the resin composition for copper clad laminates: the maleimide resin can specifically be one or a mixture of two or more of the maleimide resins of model DFE930, DFE936, and DFE939 produced by Sichuan Dongcai Technology Group Co., Ltd., or other commercially available products.

[0044] Another content of the present invention is: a method for preparing a resin composition for copper-clad laminates, characterized in that: 100 parts by mass of a low-dielectric, high-peel strength hydrocarbon resin, 10 to 20 parts by mass of a maleimide resin, 0.1 to 0.5 parts by mass of an initiator, 0.1 to 0.5 parts by mass of an antioxidant, 60 to 80 parts by mass of a filler and 70 to 140 parts by mass of a solvent are mixed and stirred uniformly at a temperature of 30 to 50° C., thereby preparing the resin composition for copper-clad laminates;

[0045] The solid content of the copper clad laminate composition is 58% to 75%;

[0046] The solid content is defined as the weight percentage of the solid content in the solution to the total solution.

[0047] The resin composition for copper-clad laminates of the present invention (prepared) is used to prepare copper-clad laminates, and the steps are as follows:

[0048] a. Preparation of prepreg: Select a smooth and clean E-glass fiber cloth with a thickness of 0.2 mm, impregnate the above-mentioned resin composition (solution) for copper-clad laminates (prepared) of the present invention, take it out, and then bake it in an oven at 130-170° C. for 4-7 minutes; the resin weight percentage content of the prepreg is preferably 62%-68%;

[0049] b. Preparation of copper clad laminate: overlap the above-mentioned prepreg cut pieces, cover copper foil on both sides or one side of the prepreg, and then place it in a hot press, maintain the heating rate at 1-3°C / min, and after reaching the temperature, press at 0.2-1MPa pressure and 80-150°C temperature for 1-3 hours, then continue to heat, maintain the heating rate at 1-3°C / min, and after reaching the temperature, press at 2-7MPa pressure and 180-250°C temperature for 1-6 hours. The RC of the board is 60±2%.

[0050] Compared with the prior art, the present invention has the following characteristics and beneficial effects:

[0051] (1) The low dielectric and high peel strength hydrocarbon resin of the present invention adopts a free radical polymerization reaction between a double bond-containing phenolic compound and divinylbenzene in the presence of a free radical initiator, an inhibitor, and a solvent, and introduces phenolic hydroxyl groups into the hydrocarbon resin structure, thereby increasing the polar groups of the resin and increasing the peel strength between the resin cured product and the copper foil;

[0052] (2) The low dielectric and high peel strength hydrocarbon resin composition of the present invention introduces a maleimide resin with good structural symmetry and rigidity, so that the dielectric constant and dielectric loss of the product are further reduced; at the same time, the heat resistance of the product is further improved due to the introduction of a highly heat-resistant imide ring;

[0053] (3) The low-dielectric and high-peel strength hydrocarbon resin composition of the present invention is used. After pressing, the peel strength is ≥1.5N / mm; the glass transition temperature Tg is ≥245°C; the dielectric constant is ≤2.8 (10GHz); the dielectric loss is ≤0.0025 (10GHz); it has the characteristics of high peel strength, low dielectric constant, low dielectric loss, high glass transition temperature, etc. and can be used as a resin for high-performance copper clad laminates;

[0054] (4) The preparation process of the product of the present invention is simple, and the copper clad laminate material obtained by using the present invention has good heat resistance, low dielectric constant and dielectric loss factor, and high peel strength; the resin composition for copper clad laminates of the present invention can be used in laminates, integrated circuit packaging, high-frequency and high-speed copper clad laminates, high-density Internet, artificial intelligence, 5G base stations, power amplifiers and automotive radars, etc., and the product performance is good and the practicability is strong. DETAILED DESCRIPTION

[0055] The following embodiments are intended to further illustrate the present invention, but should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0056] Part I Preparation of Low Dielectric and High Peel Strength Hydrocarbon Resins

[0057] Embodiments 1-1 to 1-6:

[0058] A method for preparing a low dielectric and high peel strength hydrocarbon resin, comprising the following steps:

[0059] The first step is to introduce nitrogen into a reactor equipped with a stirrer, a thermometer, and a condenser, add 1 mol of divinylbenzene, 0.1-0.5 mol of a phenolic compound containing a double bond, then add a free radical initiator of 0.1-2% of the total weight of the divinylbenzene and the phenolic compound containing a double bond, add a polymerization inhibitor of 0.01-1% of the total weight of the divinylbenzene and the phenolic compound containing a double bond, add a solvent of twice the total weight of the divinylbenzene and the phenolic compound containing a double bond, raise the temperature to 60-100° C., react for 1-10 hours, and obtain a hydrocarbon resin solution with low dielectric and high peel strength;

[0060] In the second step, the distillation temperature is maintained at 60-100° C., and the solvent and unreacted divinylbenzene in the hydrocarbon resin solution are evaporated by rotary evaporation to obtain a low dielectric and high peel strength hydrocarbon resin.

[0061] The specific components, raw materials, dosage (unit: kg) and process parameters of each embodiment in Examples 1-1 to 1-6 are shown in Table 1 below.

[0062] Table 1:

[0063]

[0064]

[0065] Part 2 Preparation of Resin Composition for Copper Clad Laminates

[0066] Embodiment 2-1~2-6:

[0067] The invention discloses a resin composition for copper-clad laminates and a preparation method thereof. The resin composition for copper-clad laminates is prepared by uniformly mixing 100 parts by weight of a low-dielectric and high-peel strength hydrocarbon resin, 10 to 20 parts by weight of a maleimide resin, 0.1 to 0.5 parts by weight of an initiator, 0.1 to 0.5 parts by weight of an antioxidant, 60 to 80 parts by weight of a filler and 70 to 140 parts by weight of a solvent at 30 to 50° C.

[0068] The specific components, raw materials, and amounts (unit: g) of each example in Examples 2-1 to 2-6 are shown in Table 2 below.

[0069] Table 2:

[0070]

[0071] The resin composition for copper clad laminate prepared in the above Examples 2-1 to 2-6 is used to prepare a copper clad laminate, and the steps are as follows:

[0072] a. Preparation of prepreg: Select a smooth and clean E-glass cloth with a thickness of 0.2 mm, impregnate it with the resin composition (solution) for copper clad laminate prepared in the above Examples 2-1 to 2-6, take it out, and then bake it in an oven at 130 to 170° C. for 4 to 7 minutes;

[0073] b. Preparation of copper clad laminate: overlap the above-mentioned prepreg cut pieces, cover copper foil on both sides or one side of the prepreg, and then place it in a hot press, maintain the heating rate at 1-3°C / min, and after reaching the temperature, press at 0.2-1MPa pressure and 80-150°C temperature for 1-3 hours, then continue to heat, maintain the heating rate at 1-3°C / min, and after reaching the temperature, press at 2-7MPa pressure and 180-250°C temperature for 1-6 hours. The RC of the board is 60±2%.

[0074] The resin compositions for copper clad laminates prepared in the above Examples 2-1 to 2-6 are used to prepare copper clad laminates. The technical performance comparison between the prepared copper clad laminates and the comparative examples is shown in Table 3 below:

[0075] Table 3:

[0076]

[0077] Note: The data in Table 3 are the test data after the low dielectric and high peel strength hydrocarbon resin is pressed into the copper clad laminate.

[0078] Comparative Examples 1 and 2 are test data of purchased hydrocarbon resin copper clad laminates.

[0079] The technical performance test methods in Table 3 are as follows:

[0080] (1) Dielectric constant

[0081] The dielectric constant at 10 GHz was measured using the flat plate method according to 2.5.5.9 of IPC-TM-650.

[0082] (2) Dielectric loss factor tangent

[0083] According to 2.5.5.9 of IPC-TM-650, use the flat plate method to measure the dielectric loss tangent at 10 GHz.

[0084] (3) Peel strength

[0085] The peel strength of the metal cover layer is tested according to the experimental conditions of "thermal stress" in the method specified in 2.4.8 of IPC-TM-650.

[0086] (4) Glass transition temperature (Tg)

[0087] The determination was carried out by differential scanning calorimetry according to the DSC method specified in 2.4.25 of IPC-TM-650.

[0088] It can be seen from Table 3 that the copper clad laminate material obtained by applying the embodiments of the present invention has excellent heat resistance, low dielectric constant and dielectric loss factor, and high peel strength; the resin composition for copper clad laminates of the present invention can be used in laminates, integrated circuit packaging, high-frequency and high-speed copper clad laminates, high-density Internet, artificial intelligence, 5G base stations, power amplifiers and automotive radars, and has broad application prospects.

[0089] Embodiment 3:

[0090] A low dielectric, high peel strength hydrocarbon resin, characterized in that the low dielectric, high peel strength hydrocarbon resin (compound) has the chemical structural formula shown in (3):

[0091]

[0092] In formula (3), x is 10 to 40, y is 1 to 8, R3 is -CH3, and R4 is n=0, 1, 2, R5 is -OCH3;

[0093] The number average molecular weight (Mn) of the low dielectric and high peel strength hydrocarbon resin is in the range of 2000 to 8000, and the double bond content is in the range of 20% to 60%;

[0094] The double bond content is defined as the percentage of the mass of double bonds contained in 1g of sample (ie, the hydrocarbon resin) to the total mass.

[0095] Embodiment 4:

[0096] A method for preparing a low dielectric and high peel strength hydrocarbon resin comprises the following steps:

[0097] The first step is to introduce nitrogen into a reactor equipped with a stirrer, a thermometer, and a condenser, add 1 mol of divinylbenzene, 0.1 mol of a phenolic compound containing a double bond, then add a free radical initiator of 0.1% of the total weight of the divinylbenzene and the phenolic compound containing a double bond, add a polymerization inhibitor of 0.01% of the total weight of the divinylbenzene and the phenolic compound containing a double bond, add a solvent of 2 times the total weight of the divinylbenzene and the phenolic compound containing a double bond, raise the temperature to 60° C., react for 10 hours, and obtain a hydrocarbon resin solution with low dielectric and high peel strength;

[0098] In the second step, the distillation temperature is maintained at 60° C., and the solvent and unreacted divinylbenzene in the hydrocarbon resin solution are evaporated by rotary evaporation to obtain a low dielectric and high peel strength hydrocarbon resin.

[0099] Embodiment 5:

[0100] A method for preparing a low dielectric and high peel strength hydrocarbon resin comprises the following steps:

[0101] The first step is to introduce nitrogen into a reactor equipped with a stirrer, a thermometer, and a condenser, add 1 mol of divinylbenzene, 0.5 mol of a phenolic compound containing a double bond, then add a free radical initiator of 2% of the total weight of the divinylbenzene and the phenolic compound containing a double bond, add a polymerization inhibitor of 1% of the total weight of the divinylbenzene and the phenolic compound containing a double bond, add a solvent of 2 times the total weight of the divinylbenzene and the phenolic compound containing a double bond, raise the temperature to 100° C., react for 1 hour, and obtain a hydrocarbon resin solution with low dielectric and high peel strength;

[0102] In the second step, the distillation temperature is maintained at 100° C., and the solvent and unreacted divinylbenzene in the hydrocarbon resin solution are evaporated by rotary evaporation to obtain a low dielectric and high peel strength hydrocarbon resin.

[0103] Embodiment 6:

[0104] A method for preparing a low dielectric and high peel strength hydrocarbon resin comprises the following steps:

[0105] The first step is to introduce nitrogen into a reactor equipped with a stirrer, a thermometer, and a condenser, add 1 mol of divinylbenzene, 0.3 mol of a phenolic compound containing a double bond, then add a free radical initiator of 0.1% of the total weight of the divinylbenzene and the phenolic compound containing a double bond, add a polymerization inhibitor of 0.5% of the total weight of the divinylbenzene and the phenolic compound containing a double bond, add a solvent of 2 times the total weight of the divinylbenzene and the phenolic compound containing a double bond, raise the temperature to 80° C., react for 6 hours, and obtain a low dielectric and high peel strength hydrocarbon resin solution;

[0106] In the second step, the distillation temperature is maintained at 80° C., and the solvent and unreacted divinylbenzene in the hydrocarbon resin solution are evaporated by rotary evaporation to obtain a low dielectric and high peel strength hydrocarbon resin.

[0107] In the above-mentioned embodiments 4-6:

[0108] The divinylbenzene is one of o-divinylbenzene, m-divinylbenzene and p-divinylbenzene or a mixture of two or more thereof;

[0109] The double-bond-containing phenolic compound is a compound containing a phenolic hydroxyl group, a double bond and a benzene ring structure, and has a chemical structure shown in formula (1):

[0110]

[0111] In formula (1): R1 is -CH=CH2, -CH2-CH=CH2, -C(=CH2)-CH3, -CH2-CH2-CH=CH2, -CH2-CH2=CH-CH2; R2 is -OCH3;

[0112] The free radical initiator is a peroxide or / and an azo compound initiator; specifically, one or a mixture of two or more of diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, dicyclohexyl peroxydicarbonate, isopropylbenzene hydroperoxide, and azobisisobutyronitrile;

[0113] The polymerization inhibitor is a polyphenol polymerization inhibitor or / and a quinone polymerization inhibitor, specifically one or a mixture of two or more of hydroquinone, p-tert-butylcatechol, 2,6-di-tert-butyl-p-methylphenol, p-benzoquinone, and 1,4-naphthoquinone;

[0114] The solvent is one of methanol, ethanol, tetrahydrofuran, toluene, xylene, petroleum ether, butanone, methyl isobutyl ketone or a mixture of two or more thereof.

[0115] Embodiment 7:

[0116] The resin composition for copper-clad laminates is prepared by mixing and stirring 100 parts by mass of a low-dielectric, high-peel strength hydrocarbon resin, 15 parts by mass of a maleimide resin, 0.3 parts by mass of an initiator, 0.3 parts by mass of an antioxidant, 70 parts by mass of a filler and 105 parts by mass of a solvent at 40°C to obtain the resin composition for copper-clad laminates.

[0117] Embodiment 8:

[0118] The resin composition for copper-clad laminates is prepared by mixing and stirring 100 parts by mass of a low-dielectric and high-peel strength hydrocarbon resin, 10 parts by mass of a maleimide resin, 0.1 parts by mass of an initiator, 0.1 parts by mass of an antioxidant, 60 parts by mass of a filler and 70 parts by mass of a solvent at 30°C to obtain the resin composition for copper-clad laminates.

[0119] Embodiment 9:

[0120] The resin composition for copper-clad laminates is prepared by mixing and stirring 100 parts by mass of a low-dielectric and high-peel strength hydrocarbon resin, 20 parts by mass of a maleimide resin, 0.5 parts by mass of an initiator, 0.5 parts by mass of an antioxidant, 80 parts by mass of a filler and 140 parts by mass of a solvent at 50°C to obtain the resin composition for copper-clad laminates.

[0121] In the above-mentioned embodiments 7-9:

[0122] The low dielectric and high peel strength hydrocarbon resin has a general chemical structure as shown in formula (4):

[0123]

[0124] In formula (4), x is 10 to 40, y is 1 to 8, R3 is -CH3, and R4 is n=0, 1, 2; R5 is -OCH3;

[0125] The low dielectric and high peel strength hydrocarbon resin may be the low dielectric and high peel strength hydrocarbon resin prepared in any one of Examples 1-1 to 1-6;

[0126] The maleimide resin has a general chemical structure as shown in formula (5):

[0127]

[0128] In formula (5): R6, R7 are -H, -CH3, -C2H5;

[0129] The maleimide resin may be one or a mixture of two or more of the maleimide resins of model DFE930, DFE936, and DFE939 of Sichuan Dongcai Technology Group Co., Ltd.;

[0130] The antioxidant is one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], 2,6-di-tert-butyl-p-cresol, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate isooctyl alcohol ester, bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate][oxalylbis(azanediyl)]bis(ethane-2,1-diyl)ester, or a mixture of two or more thereof;

[0131] The filler is one or a mixture of two or more of montmorillonite, calcium carbonate, magnesium hydroxide, zinc borate, talc, aluminum hydroxide, kaolin, barium sulfate, silicon dioxide, silicon micropowder, mica powder, hollow glass microspheres, and fumed silica;

[0132] The solvent is one or a mixture of two or more of butanone, toluene, xylene, cyclohexanone, propylene glycol monomethyl ether, propylene glycol methyl ether acetate, N,N-dimethylformamide, N,N-dimethylacetamide, and methyl isobutyl ketone;

[0133] The initiator is a peroxide or / and an azo compound initiator; specifically, one or a mixture of two or more of diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, dicyclohexyl peroxydicarbonate, isopropylbenzene hydroperoxide, and azobisisobutyronitrile.

[0134] In the above embodiments: the percentages used, unless otherwise specified, are all weight (mass) percentages or percentages known to those skilled in the art; the proportions used, unless otherwise specified, are all weight (weight) proportions; the weight parts may be grams or kilograms.

[0135] In the above embodiments, the process parameters (temperature, time, pressure, etc.) in each step and the numerical values ​​of the amounts of each component are ranges, and any point can be applied.

[0136] The technical contents not specifically described in the present invention and the above embodiments are the same as the prior art, and the raw materials are all commercially available products.

[0137] The present invention is not limited to the above embodiments, and all of the contents of the present invention can be implemented and have the above good effects.

Claims

1. Low dielectric, high peel strength hydrocarbon resin, characterized by: The low dielectric, high peel strength hydrocarbon resin has the chemical structure shown in (3): In formula (3), x is 10 to 40, y is 1 to 8, R3 is -CH3, and R4 is n=0, 1, 2, R5 is -OCH3.

2. The low dielectric, high peel strength hydrocarbon resin according to claim 1, characterized in that: The number average molecular weight of the low dielectric and high peel strength hydrocarbon resin is in the range of 2000 to 8000, and the double bond content is in the range of 20% to 60%.

3. The low dielectric, high peel strength hydrocarbon resin according to claim 1, characterized in that: The preparation method of the low dielectric and high peel strength hydrocarbon resin is as follows: divinylbenzene and a phenolic compound containing a double bond are polymerized in the presence of a free radical initiator, an inhibitor and a solvent to obtain a low dielectric and high peel strength hydrocarbon resin solution, and the solvent and unreacted raw materials in the solution are then evaporated to obtain the low dielectric and high peel strength hydrocarbon resin.

4. The low dielectric, high peel strength hydrocarbon resin according to claim 3, characterized in that: The steps of the preparation method of the low dielectric and high peel strength hydrocarbon resin are as follows: The first step is to introduce nitrogen into a reactor equipped with a stirrer, a thermometer, and a condenser, add 1 mol of divinylbenzene, 0.1-0.5 mol of a phenolic compound containing a double bond, then add a free radical initiator of 0.1-2% of the total weight of the divinylbenzene and the phenolic compound containing a double bond, add a polymerization inhibitor of 0.01-1% of the total weight of the divinylbenzene and the phenolic compound containing a double bond, add a solvent of twice the total weight of the divinylbenzene and the phenolic compound containing a double bond, raise the temperature to 60-100° C., react for 1-10 hours, and obtain a hydrocarbon resin solution with low dielectric and high peel strength; In the second step, the distillation temperature is maintained at 60-100° C., and the solvent and unreacted divinylbenzene in the hydrocarbon resin solution are evaporated by rotary evaporation to obtain a low dielectric and high peel strength hydrocarbon resin.

5. The low dielectric, high peel strength hydrocarbon resin according to claim 4, characterized in that: The divinylbenzene is one of o-divinylbenzene, m-divinylbenzene and p-divinylbenzene or a mixture of two or more thereof; The double-bond-containing phenolic compound is a compound containing a phenolic hydroxyl group, a double bond and a benzene ring structure, and has a chemical structure shown in formula (1): In formula (1): R1 is -CH=CH2, -CH2-CH=CH2, -C(=CH2)-CH3, -CH2-CH2-CH=CH2, -CH2-CH2=CH-CH2; R2 is -OCH3; The free radical initiator is a peroxide or / and an azo compound initiator; The polymerization inhibitor is a polyphenol polymerization inhibitor and / or a quinone polymerization inhibitor.

6. The low dielectric, high peel strength hydrocarbon resin according to claim 5, characterized in that: The free radical initiator is one or a mixture of two or more of diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, dicyclohexyl peroxydicarbonate, isopropylbenzene hydroperoxide, and azobisisobutyronitrile; The polymerization inhibitor is one or a mixture of two or more of hydroquinone, p-tert-butylcatechol, 2,6-di-tert-butyl-p-methylphenol, p-benzoquinone, and 1,4-naphthoquinone; The solvent is one of methanol, ethanol, tetrahydrofuran, toluene, xylene, petroleum ether, butanone, methyl isobutyl ketone or a mixture of two or more thereof.

7. A resin composition for copper-clad laminates, characterized in that: The resin composition for copper clad laminate is prepared by mixing and stirring 100 parts by weight of a low dielectric and high peel strength hydrocarbon resin, 10 to 20 parts by weight of a maleimide resin, 0.1 to 0.5 parts by weight of an initiator, 0.1 to 0.5 parts by weight of an antioxidant, 60 to 80 parts by weight of a filler and 70 to 140 parts by weight of a solvent at 30 to 50° C. to obtain the resin composition for copper clad laminate; The low dielectric and high peel strength hydrocarbon resin has a general chemical structure as shown in formula (4): In formula (4), x is 10 to 40, y is 1 to 8, R3 is -CH3, and R4 is n=0, 1, 2; R5 is -OCH3; The maleimide resin has a general chemical structure as shown in formula (5): In formula (5): R6, R7 are -H, -CH3, -C2H5; The initiator is a peroxide or / and an azo compound initiator; The antioxidant is one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], 2,6-di-tert-butyl-p-cresol, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate isooctyl alcohol ester, bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate][oxalylbis(azanediyl)]bis(ethane-2,1-diyl)ester, or a mixture of two or more thereof; The filler is one or a mixture of two or more of montmorillonite, calcium carbonate, magnesium hydroxide, zinc borate, talc, aluminum hydroxide, kaolin, barium sulfate, silicon dioxide, silicon micropowder, mica powder, hollow glass microspheres, and fumed silica; The solvent is one or a mixture of two or more of butanone, toluene, xylene, cyclohexanone, propylene glycol monomethyl ether, propylene glycol methyl ether acetate, N,N-dimethylformamide, N,N-dimethylacetamide and methyl isobutyl ketone.

8. The resin composition for copper-clad laminate according to claim 7, characterized in that: The initiator is one of diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, dicyclohexyl peroxydicarbonate, isopropylbenzene hydroperoxide and azobisisobutyronitrile, or a mixture of two or more thereof.

9. The resin composition for copper-clad laminate according to claim 7 or 8, characterized in that: The maleimide resin is one or a mixture of two or more maleimide resins of models DFE930, DFE936 and DFE939 produced by Sichuan Dongcai Technology Group Co., Ltd.

10. The method for preparing the resin composition for copper-clad laminate according to claim 7, characterized in that: 100 parts by weight of a low dielectric and high peel strength hydrocarbon resin, 10 to 20 parts by weight of a maleimide resin, 0.1 to 0.5 parts by weight of an initiator, 0.1 to 0.5 parts by weight of an antioxidant, 60 to 80 parts by weight of a filler and 70 to 140 parts by weight of a solvent are mixed and stirred uniformly at a temperature of 30 to 50° C. to obtain a resin composition for a copper clad laminate.

Citation Information

Patent Citations

  • Homogeneous dispersion liquid of cross-linkable hydrocarbon resin composition, prepreg prepared from homogeneous dispersion liquid, and high-thermal-conductivity thermosetting copper-clad plate

    CN112111074A

  • High-hardness, high-peel-strength and yellowing-resistant hydrocarbon resin composition as well as preparation method and application thereof

    CN113980370A

Cited By

  • Self-toughening hydrocarbon copolymer for high-frequency high-speed copper-clad plate and preparation method of self-toughening hydrocarbon copolymer

    CN119930892A

  • Acenaphthene alkenyl fluorine-containing hydrocarbon resin for M9-grade copper-clad plate and preparation method thereof

    CN121949685A